2019
DOI: 10.1021/acs.nanolett.9b03022
|View full text |Cite
|
Sign up to set email alerts
|

Solving the Thermoelectric Trade-Off Problem with Metallic Carbon Nanotubes

Abstract: Semiconductors are generally considered far superior to metals as thermoelectric materials because of their much larger Seebeck coefficients (S). However, a maximum value of S in a semiconductor is normally accompanied by a minuscule electrical conductivity (σ), and hence, the thermoelectric power factor (P = S 2σ) remains small. An attempt to increase σ by increasing the Fermi energy (E F), on the other hand, decreases S. This trade-off between S and σ is a well-known dilemma in developing high-performance th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(81 citation statements)
references
References 29 publications
4
77
0
Order By: Relevance
“…[37] The purity was determined to be 93.2 ± 0.4% by an optical procedure. [38] Measuring Absorbance: The absorption spectra of SWCNT films were measured by a UV-visible-near-infrared spectrometer (Agilent Cary 5000). In detail, the SWCNT film was transferred from the filter to a quartz substrate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[37] The purity was determined to be 93.2 ± 0.4% by an optical procedure. [38] Measuring Absorbance: The absorption spectra of SWCNT films were measured by a UV-visible-near-infrared spectrometer (Agilent Cary 5000). In detail, the SWCNT film was transferred from the filter to a quartz substrate.…”
Section: Methodsmentioning
confidence: 99%
“…To demonstrate how the coloration model works, we first produced a solution-filtrated film enriched with (6,5) SWCNTs. [35][36][37][38] We then compared the OAS and its color calculated using the coloration model (Figure 2a). The spectra were normalized by the first transition (S 11 ) peak.…”
mentioning
confidence: 99%
“…Besides, Ichinose et al 32 suggested that the alignment of SWCNTs led to an enhanced σ but unchanged S for the aligned metallic film (sample #5), and a PF value of around 300 μW m −1 K −2 was achieved. Similar conclusion was also drawn in the study by Fukuhara et al 33 on SWCNT film (a mixture of metallic and semiconducting SWCNTs).…”
Section: Carbon Materials As Thermoelectric Materialsmentioning
confidence: 99%
“…Moreover, a 2D film with a high‐purity ensemble of (6,5) s‐SWNTs was used for the thermoelectricity device by Yanagi's group. [ 85 ] Because of the recent progress for the synthesis of high‐quality carbon nanotubes, the control of the diameter with a specific (n,m) s‐SWNT is possible. [ 86–88 ] Hopefully, a single chirality s‐SWNT sample will give much a higher value for PF.…”
Section: Experimental Evidencesmentioning
confidence: 99%